Rapidly involuting congenital hemangioma associated with Kasabach-Merritt Syndrome - Ballona, Rosalia; Zevallos, Jean; Núñez, Jeanette (Journal of Advanced Pediatrics and Child Health, 2021)
Background: Rapidly involuting congenital hemangioma (RICH) is a rare vascular tumor that is present at birth and involutes during the first year of life. Kasabach-Merritt syndrome (KMS) is a complication of some vascular tumors such as kaposiform hemangioendothelioma and tufted angioma associated with thrombocytopenia and coagulopathy. Results: The case of a 2-month-old infant with a diagnosis of RICH with thrombocytopenia and coagulation disorder, successfully treated with surgical excision without complications or recurrence is presented. Conclusion: The association between RICH and KMS is rare. Histopathological study, immunohistochemistry and ultrasound findings are important for the diagnosis. Brief summary: This report covers the rare association between rapidly involuting congenital hemangioma and Kasabach-Merritt syndrome in a 2-months-old female infant.